2005
DOI: 10.1354/vp.42-5-665
|View full text |Cite
|
Sign up to set email alerts
|

Putative Metronidazole Neurotoxicosis in a Cat

Abstract: Abstract.A presumptive case of metronidazole toxicity in a 3.4-kg adult cat is described. The cat had been treated for suspected inflammatory bowel disease with an anti-inflammatory dose of prednisone and metronidazole (73.5-147 mg/kg PO q24h) for approximately 40 days prior to presentation. Clinical signs were primarily related to the central nervous system, including acute tetraparesis, unresponsiveness, tremors, and vocalization. The patient was euthanatized after 12 days of supportive care. Necropsy reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
2
18
0
7
Order By: Relevance
“…[19][20][21][22] A toxicologic study 19 in rats demonstrated well-demarcated usually symmetric lesions in the vestibular nuclei, cochlear nuclei, rostral colliculus, cerebellar nuclei, and olivary nuclei after the administration of high doses of metronidazole, and these lesions were characterized as spongiform changes within neurons. A similar experimental study in dogs demonstrated the degeneration and selective loss of Purkinje cells 20 and mild swelling of axon sheaths in vestibular-cerebellar white matter tracts and leukomalacia near the vestibular nerve radix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] A toxicologic study 19 in rats demonstrated well-demarcated usually symmetric lesions in the vestibular nuclei, cochlear nuclei, rostral colliculus, cerebellar nuclei, and olivary nuclei after the administration of high doses of metronidazole, and these lesions were characterized as spongiform changes within neurons. A similar experimental study in dogs demonstrated the degeneration and selective loss of Purkinje cells 20 and mild swelling of axon sheaths in vestibular-cerebellar white matter tracts and leukomalacia near the vestibular nerve radix.…”
Section: Discussionmentioning
confidence: 99%
“…21 According to a recent study in cats, multifocal well-demarcated foci of necrosis were present in central brain stem regions from the diencephalon to the medulla oblongata. 22 However, no documented data are available B A C Fig 2. A 55-year-old man with ischemic colitis (patient 6). A, Axial T2-weighted (TR/ TE ϭ 5000/110) images demonstrate bilateral symmetric hyperintense lesions in the dorsal medulla, vestibular, abducens, and focal tegmental lesions of the superior olivary nuclei of the dorsal pons, dentate nuclei of the cerebellum, the tectum of the midbrain, and the splenium of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Os achados histopatológicos incluem degeneração e desmielinização axonal (GREAVES, 2000), perda de células de Purkinje cerebelares (MARCH, 2003), edema de axônios da substância branca dos tratos vestibular-cerebelar e leucomalácia próximo à raiz do nervo vestibular (OLSON et al, 2005).…”
Section: Relato De Casounclassified
“…Estas áreas continham marcante aumento do número de macrófagos e células da micróglia, principalmente células gitter, muitos contendo material granular fagocitado. Alguns eosinófilos foram verificados, pequenos glóbulos arredondados de mielina degenerada de coloração escura e eosinofílica e aumento de capilares, frequentemente com células endoteliais discretamente edemaciadas (OLSON et al, 2005).…”
Section: Relato De Casounclassified
See 1 more Smart Citation